2017
DOI: 10.5817/cp2017-1-9
|View full text |Cite
|
Sign up to set email alerts
|

Let’s talk about sex: How people with intellectual disability in Australia engage with online social media and intimate relationships

Abstract: People with intellectual disability often experience repression and control of their sexuality as they have historically been perceived as being childlike and asexual by members of society.  Such acts can be seen to contravene their Human Rights under The Convention on the Rights of Person with Disabilities (CRPD), which endorses the rights of people with intellectual disability to fully express their sexuality.The purpose of this study was to explore if people with intellectual disability access internet base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 45 publications
(69 reference statements)
0
30
0
2
Order By: Relevance
“…Hollomotz & Speak‐up Committee (2009) conducted four focus groups with service users of an NHS intellectual disabilities service, which highlighted the difficulties people face when seeking the privacy to explore sexual relationships, especially when living in communal accommodation. Australian research (Darragh et al., 2017) where adults with intellectual disabilities were interviewed about their Internet use found that people could conduct themselves safely without any specific training. There are other, wider challenges for people with intellectual disabilities who are looking to engage in sexual relationships, which include issues around capacity and the law (Evans & Rodgers, 2000), the impact of social and cultural norms ascribed to people with intellectual disabilities and perceptions of their sexuality (Azzopardi‐Lane & Callus, 2015), and structural and organizational rules that may also preclude facilitating relationships between service users (Lesseliers, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Hollomotz & Speak‐up Committee (2009) conducted four focus groups with service users of an NHS intellectual disabilities service, which highlighted the difficulties people face when seeking the privacy to explore sexual relationships, especially when living in communal accommodation. Australian research (Darragh et al., 2017) where adults with intellectual disabilities were interviewed about their Internet use found that people could conduct themselves safely without any specific training. There are other, wider challenges for people with intellectual disabilities who are looking to engage in sexual relationships, which include issues around capacity and the law (Evans & Rodgers, 2000), the impact of social and cultural norms ascribed to people with intellectual disabilities and perceptions of their sexuality (Azzopardi‐Lane & Callus, 2015), and structural and organizational rules that may also preclude facilitating relationships between service users (Lesseliers, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…In accordance with the present results, previous studies demonstrated how the access, interaction and participation to SNS affect the lives of PID in various ways. Thereby, many authors discussed the motives of PID for using SNS (e.g., desire to meet new people or romantic partner; (Amado et al, 2013;Darragh et al, 2017;Löfgren-Mårtenson, 2008), the potentials of SNS for the impaired individuals (e.g., expressing a social identity online by self-generating content (Holmes & O'Loughlin, 2014) as well as the challenges regarding the SNS usage (e.g., cyberbullying; Holmes & O'Loughlin, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Söderstrom's study (2009) confirms this assumption: participants with disabilities intentionally use the Internet to establish social contacts with peers outside their milieu. Additionally, some PID also use SNS to find romantic partners and build intimate relationships (Darragh et al, 2017;Löfgren-Mårtenson, 2008). SNS also serve as a means of expressing social identity as well as sharing life stories, personal experiences and opinions (Caton & Chapman, 2016;Chadwick & Wesson, 2016;Chadwick et al, 2019).…”
Section: Online Access Interaction and Participation Of People With Intellectual Disabilitiesmentioning
confidence: 99%
“…As young adults with ID transition from child to adult services tensions are evident regarding the expression of their sexuality due to concerns regarding the risks associated with exploitation versus the right to experience relationships and intimacy [ 25 , 26 ]. However, concerns exist around an individual’s lack of knowledge about relationships and appropriate sexual behaviours [ 27 ]. There may also be limited awareness of the potential risks of exploitation and abuse, unintended pregnancy and HIV and STIs [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%